(untitled) (Baghdad Science Journal, 2024)
Targeting the hepcidin-ferroportin axis is the key mechanism involved in metabolic health. This study aims to investigate the intertwined relationship between vitamin D status and iron homeostasis in metabolic syndrome induced by a high-fat high-fructose (HFHF) diet in rats. The experimental groups were as follows: G1; negative control, G2; positive control, G3 and G4 (balanced diet and supplemented with Vit.D3 (12 and 24 µg/Kg b.wt respectively twice/week). G5 and G6 (HFHF diet and supplemented with Vit.D3 (12 and 24 µg/Kg b.wt respectively twice/week). Various biochemical, molecular, and histological parameters were evaluated in serum and liver tissue homogenate. The results showed that Vit.D3 administration significantly modulated the disrupted iron homeostasis induced by the HFHF diet through downregulation of hepatic hepcidin and upregulation of ferroportin-1 protein expression which leads to significant improvement in serum iron profile. Vit.D3 administration also, enhanced antioxidant status by reducing elevated serum levels of malondialdehyde and increasing hemeoxygenase-1 activity. In addition to, upregulating nuclear factor erythroid 2-related factor 2 gene expression. Also, it attenuated elevated serum inflammatory biomarkers and resistin level while, significantly elevated serum adiponectin level. Furthermore, vitamin D receptor expression was upregulated in liver tissue and serum Vit. D3 was significantly increased which ameliorated insulin resistance and disrupted lipid profile. Microscopic findings show hepatic damage, fatty infiltration while Vit.D3 administration preserved the liver tissue.